2020
DOI: 10.3390/toxins12120810
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Microcystin-LR Removal in a Real Lake Water by UV/H2O2 Treatment and Analysis of Specific Energy Consumption

Abstract: The hepatotoxin microcystin-LR (MC-LR) represents one of the most toxic cyanotoxins for human health. Considering its harmful effect, the World Health Organization recommended a limit in drinking water (DW) of 1 µg L−1. Due to the ineffectiveness of conventional treatments present in DW treatment plants against MC-LR, advanced oxidation processes (AOPs) are gaining interest due to the high redox potential of the OH• radicals. In this work UV/H2O2 was applied to a real lake water to remove MC-LR. The kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…This treatment can eliminate the bloom and MCs but needs to be optimized based on bloom density and the quantity of toxins. For toxin quantification and assistance to prevention, analytical methods, such as the one presented in this paper, would be suitable [97][98][99][100][101][102][103][104][105]. Approaches such as flock lock or flock sink techniques could be a viable solution to prevent bloom incidence by capturing phosphorous on the bottom of larger waterbodies with a greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment can eliminate the bloom and MCs but needs to be optimized based on bloom density and the quantity of toxins. For toxin quantification and assistance to prevention, analytical methods, such as the one presented in this paper, would be suitable [97][98][99][100][101][102][103][104][105]. Approaches such as flock lock or flock sink techniques could be a viable solution to prevent bloom incidence by capturing phosphorous on the bottom of larger waterbodies with a greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the application of advanced oxidation processes (AOPs) on waters is gaining interest (Vilar et al 2017 ). In fact, the production of highly reactive OH• proved to effectively remove persistent organic pollutants and recalcitrant substances (Sorlini et al 2020 ). Among the AOPs, the application of photoelectrocatalysis (PEC) on waters is still at an early stage of study, but there are several examples of laboratory-scale applications (Wei et al 2017 ; Garcia-Segura and Brillas 2017 ; Fernández-Domene et al 2018 ; Brugnera et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three other papers address different advanced oxidation processes used to remove cyanotoxins [7][8][9]. Advanced oxidation processes involve a set of oxidative water treatments, including treatment with UV-O 3 , UV-H 2 O 2 , the Fenton process, the photo-Fenton process, and nonthermal plasmas as well as sonolysis, photocatalysis, and radiolysis, all based on the production of powerful, highly reactive oxidants.…”
mentioning
confidence: 99%
“…The authors also found that the system's outstanding performance derives from the excellent photocatalytic performance and the high chemical and photochemical stability of Al-doped ZnO nanoparticles under visible-light irradiation with LEDs [8]. In another study, Sorlini et al [9] investigated the viability of using UV-H 2 O 2 to treat microcystin-LR, particularly by analyzing specific energy consumption in the waters of Lake Iseo in the Province of Brescia, Lombardy, Italy. Those authors aimed to preliminarily study the effectiveness of UV-H 2 O 2 on real water with respect to water matrix effects in order to clarify how the type of oxidant influences kinetics by analyzing the effects of the initial microcystin-LR concentration and the H 2 O 2 dosage.…”
mentioning
confidence: 99%
See 1 more Smart Citation